A pérola negra regressa ao ventre da ostra: Wilson Simonal em suas relações com Indústria Cultural (1963 a 1971) - Hartwig, Adriane Mallmann Eede (2008)
The purpose of this study is to discuss how music can both, lull moments and emotions and make possible to a historian to get closer to determinate socio-historical contexts or specific conjunctures, having as basis, the premise that the process that go through the production of an artist, or of music, is related to certain historical moments. We would like to emphasize that if this work has as central question the construction of an artist, Wilson Simonal, it is not a biography or a determinist digression about mass media, but having as a basis a case study, consisting in an analysis about the established relations between the cultural industry and the artist. This artist is seen from the various forms of living and experience that influence his image about consumption and the path of his career. In a synthesis, this work is concerned about the singer and his trajectory, that can be seen as a simple merchandize, a propagation instrument of the bourgeois values in an specific period of time, a legitimation of a State determined form, shows, through apparent attitudes, or effectively contradictory, throughout his public life, his acts as a person. Therefore, being an instrument of the system, he also uses advantage of what comes in favor of him. The time circumscription of this research, between 1963 and 1971, marks out, in general, the military civil coup of 1964 and the subsequent failure of a Force Regime in the country. Simonal became in this period a successful artist, having great popularity. We consider that his closeness to the military, the investments of multinational enterprises in his career, and the image showed of him as the hero of workers , express a dominant class project that, through means made available by the cultural industry, legitimate the regime and fundamentally, assert the capitalism as an ideal socio-economic formation. After the moment that Simonal is able not only to sell his product but also sell ideologies, other idols take his place. The cultural industry produces short-livings. For the artists to be relegate to the ostracism take on outlines of conspiracy; sectors of the artist and intellectual means see in Simonal a Regime informer, justifies the contempt that the artist needs to face. These are just examples of how an episode can be remembered in different ways, in a direct relation with the place where it is said. Concluding, the surveyed sources do not allow to establish a direct connection between the accusations that attain Simonal and the decadence of his career, and this is not the objective of this study, but, as they enable us to perceive that the Brazilian artist was forgotten quickly, make us ponder about the constitution of the memories or the structures of the forgetfulness